Effect of the Number of Blades and Variations in Position of Straight Blades on Vortex Turbine Efficiency - Ridwan Arief Subekti,; Fazila Mohd-Zawawi,; Kamarulafizam Ismail,; Setia Subekti,; Mukhtar Effendi,; Anjar Susatyo,; Ahmad Fudholi, (International Journal of Integrated Engineering, 2025)
The need for electrical energy continues to increase every year so that alternative renewable energy sources are needed. One potential renewable energy is water energy by utilizing flat river flow or very low head. Vortex turbines can be applied at very low head. This research was conducted to identify the features of the most efficient vortex turbine. From the literature review, it is known that there has been no research on the effect of the number of straight vortex turbine blades in relation to their placement in the basin hole.The research methodology was laboratory testing using five different straight blades. The runner is made of PVC material with the number of blades 3, 4, 5, 6, and 8. Tests were carried out with three variations in the position of the blades, namely the blades above the outlet hole, half submerged, and completely submerged. The water discharge used is 0.003 m3/s. Based on the test, it is known that the maximum efficiency is 33.93%, which is when the blade with a total of three blades is positioned half submerged in the outlet hole. Validation was conducted using CFD ANSYS CFX simulation where the results were relatively similar to the test. The case was simulated with a multiphase free surface model of water and air with a stationary domain on the basin and a rotating domain on the runner. The potential implication of this study is that by using a simple blade model, namely a straight model, satisfactory results can be obtained when the blade is placed correctly on the vortex turbine basin.